2022
DOI: 10.1002/ajmg.a.63027
|View full text |Cite
|
Sign up to set email alerts
|

Tissue mosaicism, FMR1 expression and intellectual functioning in males with fragile X syndrome

Abstract: Fragile X syndrome (FXS) is caused by hypermethylation of the FMR1 promoter due to the full mutation expansion (full mutation [FM]: CGG ≥ 200 repeats) and silencing of FMR1. Assessment of mosaicism for active‐unmethylated alleles has prognostic utility. This study examined relationships between FMR1 methylation in different tissues with FMR1 messenger ribonucleic acid (mRNA) and intellectual functioning in 87 males with FXS (1.89–43.17 years of age). Methylation sensitive Southern blot (mSB) and Methylation Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…In fact, we found that 30-40% of FXS(M), who based on standard PCR and Southern Blot testing are considered full mutation, fully methylated, express trace levels of FMRP in their blood. This is consistent with ndings of incomplete silencing of the FMR1 gene reported by our group and others 2,17 . In each of our recent papers, we reported a small to medium sized correlation between Deviation IQ 18 and FMRP and mRNA levels 1,2 .…”
Section: Introductionsupporting
confidence: 94%
“…In fact, we found that 30-40% of FXS(M), who based on standard PCR and Southern Blot testing are considered full mutation, fully methylated, express trace levels of FMRP in their blood. This is consistent with ndings of incomplete silencing of the FMR1 gene reported by our group and others 2,17 . In each of our recent papers, we reported a small to medium sized correlation between Deviation IQ 18 and FMRP and mRNA levels 1,2 .…”
Section: Introductionsupporting
confidence: 94%
“…The results obtained after mSB did not show an association between methylation in blood and intellectual disability. They demonstrated incomplete silencing of FMR1 in the patients with methylation mosaicism, which showed that MS-QMA gave superior results to mSB [40].…”
Section: Southern Blotmentioning
confidence: 98%
“…In mosaicism of hypermethylation, some cells exhibit hypermethylation, and others do not. In cells in which fully mutated or premutated alleles are not methylated, the FMR1 gene is transcriptionally active and can be expressed [ 90 95 ]. In male individuals, the most frequent presentation of mosaicism is non-methylation of alleles with partial mutations and either methylation or non-methylation of alleles with full mutations (i.e., a combination of mosaicism of size and mosaicism of methylation) [ 14 ].…”
Section: Molecular and Phenotypic Variabilitymentioning
confidence: 99%